A novel galacturonide from Xanthomonas campestris - Baldessari, A. (1990)
Enzyme preparations from Xanthomonas campestris incubated in the presence of UDP-[14C]GlcA and Mg2+ produced a lipophilic galacturonide with unusual properties. It was easily degraded by both mild acid treatment (0.01 M-HCl, 100°C, 10 min) and mild alkali treatment (0.06 M-NaOH, room temperature, 5 min) releasing free [14C]galacturonic acid. The galacturonide appeared to be a single compound with one negative charge, as judged by TLC, paper electrophoresis and chromotography, LH-20 gel filtration and DEAE-cellulose column chromatography. Competition experiments indicated that the true glycosyl donor was UDP-GalA, in agreement with the detection of UDP-GlcA-4-epimerase activity in the crude enzyme preparation. The transglycosidase activity was located mainly in the membrane fraction. UDP inhibited the reaction and even produced some loss of label, suggesting an easily reversible reaction. UMP had almost no effect.